2015
DOI: 10.1111/jse.12167
|View full text |Cite
|
Sign up to set email alerts
|

Using phylogenomics to resolve mega‐families: An example from Compositae

Abstract: Next-generation sequencing and phylogenomics hold great promise for elucidating complex relationships among large plant families. Here, we performed targeted capture of low copy sequences followed by nextgeneration sequencing on the Illumina platform in the large and diverse angiosperm family Compositae (Asteraceae). The family is monophyletic, based on morphology and molecular data, yet many areas of the phylogeny have unresolved polytomies and interpreting phylogenetic patterns has been historically difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 29 publications
(33 reference statements)
2
60
0
Order By: Relevance
“…The application of the NGS techniques has enabled access to large amounts of data and has helped resolve the basal polytomies in certain groups of organisms where traditional Sanger approaches using analyses of multiple‐genes failed (e.g., Graminoids, Leseber & Duvall, ; Rhinoceroses, Willerslev et al, ; Pentapetaleae, Moore et al, ; Paserida, Nabholz et al, ; Neoaves, Pacheco et al, ; Malpighiales, Xi et al, ; Commelinids, Barrett et al, ; Guenons, Guschanski et al, ; Zingiberales, Barrett et al, , Sass et al, ; Ipomeeae, Eserman et al, ; Arundinarieae, Ma et al, ; Apocynaceae, Straub et al, ; Asteraceae, Mandel et al, ; Goodeniaceae, Gardner et al, ; Columbiforms, Soares et al, ; Vitales, Zhang et al, , Wen et al, ; Eupolypod II Ferns, Wei et al, ; Hippeastreae, García et al, ; Protea , Mitchell et al, ). Most of these studies concluded in favor of the radiation hypothesis, since the NGS analysis of complete chloroplast genomes and large nuclear data sets yielded short deep branches (Leseber & Duvall, ; Moore et al, ; Nabholz et al, ; Xi et al, ; Guschanski et al, ; Straub et al, ; Mandel et al, ; Gardner et al, ; Sass et al, ; Soares et al, ; Zhang et al, ; García et al, ; Mitchell et al, ) or non‐fully resolved trees (Willerslev et al, ; Barrett et al, , ; Ma et al, ; Wei et al, ). A previous phylogenetic study based on seven DNA regions proposed a burst of diversification for the origin of the Asian Palmate group (Valcárcel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The application of the NGS techniques has enabled access to large amounts of data and has helped resolve the basal polytomies in certain groups of organisms where traditional Sanger approaches using analyses of multiple‐genes failed (e.g., Graminoids, Leseber & Duvall, ; Rhinoceroses, Willerslev et al, ; Pentapetaleae, Moore et al, ; Paserida, Nabholz et al, ; Neoaves, Pacheco et al, ; Malpighiales, Xi et al, ; Commelinids, Barrett et al, ; Guenons, Guschanski et al, ; Zingiberales, Barrett et al, , Sass et al, ; Ipomeeae, Eserman et al, ; Arundinarieae, Ma et al, ; Apocynaceae, Straub et al, ; Asteraceae, Mandel et al, ; Goodeniaceae, Gardner et al, ; Columbiforms, Soares et al, ; Vitales, Zhang et al, , Wen et al, ; Eupolypod II Ferns, Wei et al, ; Hippeastreae, García et al, ; Protea , Mitchell et al, ). Most of these studies concluded in favor of the radiation hypothesis, since the NGS analysis of complete chloroplast genomes and large nuclear data sets yielded short deep branches (Leseber & Duvall, ; Moore et al, ; Nabholz et al, ; Xi et al, ; Guschanski et al, ; Straub et al, ; Mandel et al, ; Gardner et al, ; Sass et al, ; Soares et al, ; Zhang et al, ; García et al, ; Mitchell et al, ) or non‐fully resolved trees (Willerslev et al, ; Barrett et al, , ; Ma et al, ; Wei et al, ). A previous phylogenetic study based on seven DNA regions proposed a burst of diversification for the origin of the Asian Palmate group (Valcárcel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The Asteraceae is a species-rich group that lacks reciprocal monophyly between some closely related species and genera [70], taxa that are difficult to differentiate with molecular data [71]. The Fabaceae also showed poor species resolution with all three loci (41–72%), an expected result given the number of poorly resolved genera in this family [72].…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches to handling gene tree discordance have been proposed, e.g., statistical binning of loci prior to gene tree estimation (Mirarab et al, ). One approach we have taken to begin to tackle these issues is by analyzing multi‐copy genes using a clustering approach prior to gene‐tree phylogenetic analysis (see Mandel et al, for details). Another approach would be to characterize the function of the CompCOS loci and then group multi‐gene clusters by function.…”
Section: Gene Tree Discordancementioning
confidence: 99%